Social Group Work Practice by Nongovernmental Organizations for Upliftment of People Affected and Infected by AIDS - Abraham, Mutluri (Journal of Social Work Education and Practice, 2018)
Social Group Work is a boon to the social work practitioners which make easy to work with groups. It may be challenging to initiate groups in HIV/AIDS sector due to stigma and discrimination, but few NGOs have implemented efficiently social group work practice with the HIV affected people. HIV/AIDS is one of the significant social problems in developing countries like India. It is associated with Social Stigma and Discrimination and also a barrier to the development of the nations. Support groups are an instrument for the HIV infected people to reduce stigma and discrimination and promote quality of life. Krishna District of Andhra Pradesh has been selected as a research setting for the present study. It is one of the highest HIV prevalence district in Andhra Pradesh. It is observed that six nongovernmental organizations are working in HIV/AIDS sector in Krishna District. The researcher used observation method and interacted with NGO directors, people living with HIV/AIDS, Children affected by AIDS and also grannies to know about the activities of their groups. Practical work experience of the researcher is also an additional advantage to this study. The research conducted six focus group discussions to know about the issues and challenges of different groups in HIV/AIDS sector. This article therefore will throw light upon the Social Group Work practice in various nongovernmental organizations working in HIV/AIDS sector in Andhra Pradesh. The study observed that the NGOs started groups for children, adult, and grannies affected by AIDS. In addition to that, they have also started positive networks for the people infected to solve the problems by themselves.